Chapter «Situm in loco alto et forti». Una controversia del vescovo Andrea de' Mozzi per il monastero di San Miniato - Tanzini, Lorenzo (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2021)
The essay analyses a judicial case of the late 13th century (preserved in the archival funds of the Pistoiese bishopric), in which the bishop of Florence Andrea Mozzi and the nuns of Monticelli (one of the earliest Franciscan female communities in Florence) quarrel for the rights on the church of San Miniato, under the protection of the bishop since the origin of the monastic community in the early 11th century. As usual for this kind of sources, the text provides us with an important array of informations: the references to the written records the contenders used draw an image of the documentary landscape of the monastic communities since the 11th century, and at the same time the narrative of the religious practices of the laity around the church are very well described.